CD8+ T Cells Protect During Vein Graft Disease Development - Simons, Karin H.; de Vries, Margreet R.; Peters, Hendrika A. B.; Jukema, J. Wouter; Quax, Paul H. A.; Arens, Ramon (Frontiers in Cardiovascular Medicine, 2019)
Aims: Vein grafts are frequently used conduits for arterial reconstruction in patients with cardiovascular disease. Unfortunately, vein graft disease (VGD) causes diminished patency rates. Innate immune system components are known to contribute to VGD. However, the role of T cells has yet to be established. The purpose of this study was to investigate the role of T cells and T cell activation pathways via the T cell receptor (TCR), co-stimulation and bystander effect in VGD. Methods and results Here we show upon vein graft surgery in mice depleted of CD4+ T cells or CD8+ T cells, that CD8+ T cells are locally activated and have a major protective role for vein graft patency. In presence of CD8+ T cells vein grafts appear patent while CD8+ T cell depletion results in occluded vein grafts with increases apoptosis. Importantly, the protective effect of CD8+ T cells in VGD development was TCR and co-stimulation independent. This was demonstrated in vein grafts of OT-I mice, CD70-/-, CD80/86-/- and CD70/80/86-/- mice compared to C57BL/6 mice. Interestingly, cytokines including IL-15, IL-18, IL-33 and TNF are up-regulated in vein grafts. These cytokines are cooperatively capable to activate CD8+ T cells in a bystander-mediated fashion, in contrast to CD4+ T cells. Conclusions T cells are modulators of VGD with a specific protective role of CD8+ T cells, which are locally activated in vein grafts. CD8+ T cells may protect against occlusive lesions by providing survival signals, and concert their protection independent of TCR and co-stimulation signaling.